Integration of Science and Religion: Implications for Islamic Education - Mahmudi Mahmudi; Sri Sumarni; Fahruddin Faiz (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The integration of science and religion means the fusion of science and religion. But it is not completely mixed because it has its characteristics. The integration of science and religion is likely to happen in the Islamic paradigm because it is based on the concept of tawhid. Science and religion need to cultivate awareness of holistic and comprehensive education. This study aims to explain and analyze the integration of science and religion, especially in the Islamic education system, using library research, which collects data by understanding and studying theories from various literature related to research. The results of the study concluded that the integration of science and technology has implications for Islamic education, among others: first, it has implications in terms of curriculum, delivering students the desire and ability to conduct research (research) in the fields of science to find then the